Penyelesaian Sengketa Konsumen Melalui Badan Penyelesaian Sengketa Konsumen (BPSK): Studi Efektivitas Putusan - Sopan Sopian; Aturkian Laia (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The Consumer Dispute Settlement Board (BPSK) was established as an alternative institution outside the court to resolve consumer disputes quickly, simply, and at low cost based on Law Number 8 of 1999 concerning Consumer Protection. This research examines the effectiveness of BPSK decisions focusing on normative regulation, judicial practice, and influencing factors using a descriptive-analytical normative juridical approach. The findings indicate that normatively BPSK has strong authority with final and binding decisions (Article 54 paragraph 3), yet this provision conflicts with Article 56 paragraph 2 which opens opportunities for objections to the District Court, creating legal uncertainty. In practice, BPSK decisions are often annulled by the District Court for exceeding authority, as affirmed by the Supreme Court through Decision Number 105 K/Pdt.Sus-BPSK/2026 and Permanent Jurisprudence Number 1/Yur/Perkons/2018. Inhibiting factors include overlapping authority, limited technical capacity, variation in decision quality, weak execution mechanisms, and low business actor compliance. This research recommends regulatory harmonization, granting direct execution authority to BPSK, improving human resource capacity, and strengthening BPSK's institutional status as an independent institution integrated with the national judicial system.